HUBUNGAN PELAKSANAAN SUPERVISI DENGAN DOKUMENTASI PROSES KEPERAWATAN OLEH PERAWAT PELAKSANA DI RUANG RAWAT INAP RSD dr. SOEBANDI JEMBER - Sutaryanto (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2013)
Supervision is directing activities, coaching, and evaluation of nurses in order to perform the task with different roles and functions. One function of nurses is to document the nursing process. The purpose of this research was to determine the relationship between the course of the supervision with nursing process documentation RSD Dr. Soebandi Jember. This study uses analytic survey research design with cross secional study. The number of samples in this study were 125 nurses who are members of 20 teams by using the technique of sampling purposive. Test results of Spearmen rho correlation showed the value of P <0,05, it is 0,0001, from these results can be known that there was a very significant relationship between the course of the supervision with nursing process documentation.